PpCBF6 Is Involved in Phytosulfokine α-Retarded Chilling Injury by Suppressing the Expression of PpLOX5 in Peach Fruit - Jiao, Caifeng (Frontiers in Plant Science, 2022)
The involvement of PpCBF6 in phytosulfokine α (PSKα)-ameliorated chilling injury (CI) by suppressing the expression of lipoxygenase 5 (LOX5) in peach fruit was revealed. The peaches were immersed in distilled water and PSKα solution. PSKα application inhibited the progression of CI index and weight loss, and the reduction of firmness and total soluble solids content in peaches. The superoxide anion (O2·-) production rate, hydrogen peroxide (H2O2) production and reactive oxygen species (ROS) content decreased by PSKα application. Furthermore, PSKα application reduced the LOX activity and gene expression of PpLOX5. The gene expression of PpCBF6 was also enhanced by PSKα application. Importantly, PpCBF6 bound to the C-repeat/dehydration responsive element (CRT/DRE) motif in PpLOX5 promoter, and repressed its transcription. Thus, PpCBF6 was involved in the PSKα-retarded CI by inhibiting the expression of PpLOX5 in peaches.